Anthelmintic resistance in selected goat farms in Kelantan - Basripuzi Nurul Hayyan Hassan Basri; Sani, R.A; Ariff, O.M. (2012)
The widespread use of chemical anthelmintics to control goat gastrointestinal nematodes has resulted in the occurrence of resistant nematode populations that has become a global problem including Malaysia. Faecal samples were collected from 202 goats from eight farms in Kelantan for the confirmation of gastrointestinal nematode infection. A total of 161 goats were chosen for the Faecal Egg Count Reduction Test (FECRT) to detect resistance to four anthelmintics: albendazole, ivermectin, levamisole and closantel. Varying levels of resistance were detected for each anthelmintic where resistant nematode populations to albendazole, ivermectin, levamisole and closantel were observed in goats in six, five, two and two farms, respectively. Resistance was suspected against albendazole, ivermectin and levamisole in one farm. Nematode populations in two farms were found to be susceptible to levamisole while those in only one farm was susceptible to albendazole. In the present study, levamisole was found to be the most effective anthelmintic. Pre-treatment faecal cultures revealed Haemonchus contortus (73%) as the predominant infective larvae followed by Trichostrongylus spp. (26%) and Oesophagostomum spp. (1%). Based on the present study, the anthelmintic resistance status in Kelantan is of critical concern as the current anthelmintic based nematode control in goat farms may not be effective on a long term basis. There is an urgent need to evaluate non-chemical methods to control parasitism in local goats.